Assessment of the Air Force Materiel Command Reorganization Report for Congress - Snyder, Don (RAND Corporation, 2013)
This report assesses the FY 2012 reorganization of the Air Force Material Command (AFMC), which was undertaken as one of the initiatives to achieve mandated budget reductions by eliminating civilian manpower positions, thus achieving cost savings. One AFMC challenge was to absorb these cuts with minimal, if any, impact on its assigned missions in part by targeting staff positions.